2020
DOI: 10.1111/odi.13298
|View full text |Cite
|
Sign up to set email alerts
|

Sialographic analysis of parotid ductal abnormalities associated with Sjogren's syndrome

Abstract: Objectives To analyze the location and degree of parotid ductal abnormalities associated with Sjogren's syndrome (SS) and to correlate findings with the duration of the disease. To develop a classification system based on contemporary sialography techniques and employ the system to grade findings on sialograms. To assess the role for therapeutic intervention in patients with SS. Methods Retrospective chart review of a consecutive series of 337 sialograms done by the senior investigator over a 10‐year period id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
0
19
2
Order By: Relevance
“…Patterns of structural disease identified on sialography can assist in differentiating I‐131 induced salivary gland destruction from other causes of salivary dysfunction. In contrast to the patterns identified in I‐131 sialadenitis, our previous work demonstrated that Sjogren's syndrome more commonly affects the proximal parotid ducts relative to the distal ducts, which may become involved later in the disease process 13 . The capacity to distinguish etiology of ductal pathology is particularly important for patients with autoimmune disease who undergo I‐131 therapy, as autoimmune thyroid disease and Sjogren's syndrome are the most commonly concomitant polyautoimmunities 30 .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Patterns of structural disease identified on sialography can assist in differentiating I‐131 induced salivary gland destruction from other causes of salivary dysfunction. In contrast to the patterns identified in I‐131 sialadenitis, our previous work demonstrated that Sjogren's syndrome more commonly affects the proximal parotid ducts relative to the distal ducts, which may become involved later in the disease process 13 . The capacity to distinguish etiology of ductal pathology is particularly important for patients with autoimmune disease who undergo I‐131 therapy, as autoimmune thyroid disease and Sjogren's syndrome are the most commonly concomitant polyautoimmunities 30 .…”
Section: Discussionmentioning
confidence: 87%
“…The sialograms were systematically evaluated and scored by two neuroradiologists (BP and JEM) applying the Iowa parotid sialogram scale to classify ductal stenoses/strictures, peripheral ductal dilations, and patterns of contrast retention, as previously described (Table I). 13 We adapted this classification – initially developed to address the parotid gland – to additionally apply it to submandibular gland sialography. This classification system describes location of the ductal stenosis, degree of the ductal stenosis, retention of contrast, and peripheral duct dilation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cavitary and destructive sialectasis are more prevalent in advanced cases, and punctate foci of calcifications in major salivary glands and multiple cystic or solid intraglandular masses in a miliary pattern are occasionally seen in Sjögren syndrome patients. 14 …”
Section: Discussionmentioning
confidence: 99%